Faktor-Faktor Yang Mempengaruhi Nasabah Mengadopsi Internet Banking - Ronny Ronny (BIP's JURNAL BISNIS PERSPEKTIF, 2014)
The study about adoption in internet banking by banking customer has already done by researches in Indonesia and abroad. This scientific articles is to analyse factors influence the behavior of banking customer in adopting internet banking service. The research method used was library analysis by observing research for the last five years regarding adoption of internet banking. The result of research indicated that seven variables was considered and influenced the decision of banking customer in adopting the internet banking, i.e: marketing communication, risk, security, benefit, user friendly website, trust, and banking customer experience.